TYPES AND PATTERNS OF TERRITORY IN THE TRADITIONAL SETTLEMENT OF NGATA TORO - Fuad Zubaidi (Journal of Architecture&ENVIRONMENT, 2019)
Territory in architecture is defined as a live organisms boundary to determine their demands, mark, and defend it. Territory for humans is not only limited physically and space, but also related to emotional and cultural needs.Research about territories has not been specifically studied in contexts related to cultures that have specific characteristics. Based on this, research has a focus on developing theories on the types and patterns of territories in traditional settlement.This research is naturalistic based on the theoretical framework that is built from the meaning of the results of several studies that have been conducted. In this research, the use of case studies is used as an empirical study to see how phenomena in real life of society, especially at the boundary of phenomena with existing contexts.Case Study uses a single embedded case that has more than one analysis unit. The research location is in "Ngata Toro, To-Kulawi", which is a traditional settlement that has character and characteristics. The expected outcome of this research is to develop and build concepts of patterns and types of spatial territories in architecture related to behavioral and cultural aspects.